(untitled) (Research, Society and Development, 2022)
It is increasingly important for private basic education schools to assess the extent to which they provide quality education for all, with the quality standards required by the Brazilian Constitution, so that they can improve the service provided and meet the requirements of students and all stakeholders. In addition, the search for profitability is necessary to ensure the very survival and continuity of the company. The ISO 21001 standard, published in 2018 and translated into Portuguese in 2020, is a common management tool for all organizations that provide educational products and services. The aim of this paper is to present the results of a field research of exploratory-descriptive Survey type, conducted with the purpose of assessing the level of understanding and knowledge of the ABNT NBR ISO 21001:2020 standard or its predecessor ABNT NBR 15419. The data collection instrument used was an electronic structured questionnaire, prepared on the Google Forms platform. The universe for data collection was extracted from the register of private basic education schools in the State of São Paulo, provided by the institution for which the researcher provides professional services in the private educational segment. The results obtained with the survey made it possible to understand that the directors and principals are not aware of the ISO management norms specific to the education segment. At the end, the article considers perspectives for future works, related to the difficulties or challenges in its implementation.